Gheorghe Alexa, a great personality of the Romanian leather chemistry - Monica Nănescu (Memoirs of the Scientific Sections of the Romanian Academy, 2021)
Professor Dr. Eng. Gheorghe Alexa is the founder of the higher school in the field of chemistry and leather substitutes in Romania. Author of the first treatise on raw materials and auxiliaries in the leather industry (1963), the research interests of Professor Alexa include valuing of tanning materials in Romania, vegetable tanning processes, the kinetic study of drying tanned hides, the study of mass transfer in solid-liquid extraction applied to the extraction of vegetable tannins, etc. The research, inventions and innovations of the scientist of the ”Gheorghe Asachi” Technical University of Iași attest to the special contribution Gheorghe Alexa brought to the development of leather processing technologies at European level.